Investigation of 3,3'-Diaminobenzidine-H2O2-Horseradish Peroxidase Voltammetric Enzyme-Linked Immunoassay System Used for the Detection of Prostate Specific Antigen - Yang, Jun; Bi, Caifeng; Fan, Yuhua; Zhang, Xia (Asian Journal of Chemistry, 2011)
By introducing heterocyclic compound to immunoassay systems an electrochemical substrate, a new voltammetric enzyme-linked immunoassay system of 3,3'-diaminobenzidine (DAB)-H2O2- horseradish peroxidase (HRP) has been presented and used for the sensitive detection of prostate specific antigen (PSA) in human serum. In this proposed procedure, labelled horseradish peroxidase efficiently catalyzed the oxidation reaction of 3,3'-diaminobenzidine by H2O2 and generated the electroactive product, which produced a sensitive second-order derivative linear sweep voltammetric peak at potential of -0.62V (versus SCE) in Britton-Robinson (BR) buffer solution. The free horseradish peroxidase could be measured in a linear range from 2.5 × 10-6 - 2.5 × 10-2 unit mL-1 and a detection limit of about 1.5 × 10-6 unit mL-1. Under the optimal experiment conditions, prostate specific antigen could be detected in the linear range from 0.20 to 32 ng mL-1 with a detection limit of 0.10 ng mL-1. The proposed electrochemical enzymelinked immunosorbent assay method is simple and inexpensive, which shows a promising alternative approach for detecting prostate specific antigen in the clinical diagnosis.